ANALISIS POTENSI BAHAYA DAN RISIKO TERJADINYA KEBAKARAN DAN LEDAKAN DI TANGKI PENYIMPANAN LPG PERTAMINA PERAK SURABAYA - Dani Nasirul Haqi (The Indonesian Journal of Occupational Safety and Health, 2018)
Depot LPG Pertamina Tanjung perak Surabaya is one of the companies engaged in the storage and distribution of Liquified Petroleum Gas (LPG). In the process of doing a lot of activity using chemicals that are flammable. So that the potential of fire and explosion in Depot LPG Pertamina Tanjung perak Surabaya is big. The purpose of this research is to analyze the risk of potential fire and explosion and prevention efforts that need to be done. The Dow Fire and Explosion Index Method is an instrument to evaluate the potential risks of fire, explosion, and potential reactivity of the equipment and its contents in an objective and realistic way. The results showed that the level of fire and explosion hazard in the LPG storage tank in Depot LPG Pertamina Tanjung perak Surabaya amounted to 298.62 included in the classification of a severe level of danger. The total area of exposure in case of fire and explosion is 18,352.07 m². The amount of value / price of equipment as a loss due to being in the area of exposure to hazard and exposed to fire or blasting risk in the process unit was Rp.7,237,989,100,000. The magnitude of losses due to exposure to the factor material in a particular exposure area in the unit process when the accident was Rp 8,742,767,000,000. The number of factors that can control the loss of 0.5. The amount of actual losses suffered in the case of fire and explosion amounted to Rp 4,371,383,500,000.Keywords: explosion, fire, LPG, risk analysis